Avaliação de combinação enxerto porta-enxerto de cajueiro anão precoce. - Cavalcante, Robson Assunção (2009)
We studied the interaction between stock and rootstock in the morphological and productive characteristics in dwarf cashew trees, in the stages of runner plant production and cultivation on the field, under unirrigated conditions. The experiment took place in the Planalto Farm (CIONE), located in Pio IX-Piaui, in the northeast. In November of 2004 we planted the rootstocks CP 76, CP 06, CP 09, BRS 226, CAC 38 and CAC 40, when we evaluated the seedling emergence and rootstock vigor before grafting (in January of 2005) using the clones CCP 76 e BRS 226. Sixty days after grafting, we analyzed the seedling yield and plant vigor and afterwards we transplanted them under DBC in factorial scheme (6 x 2) with four repetitions and nine plants per plot, spacing 8 m between lines and 6 m between plants. The variables of morphological development and total production were evaluated annually from 2005 to 2008, observing the characteristics of cashew nuts and pedicels from the last crop. The data was used in the analysis of variance and then compared using the means test. The use of different rootstocks affected the plant sizes and nut production and pseudofruits in early dwarf cashew trees, however it did not affect the size and the mass of cashew nuts and kernels produced. The most promising combinations are BRS 226/CAC 38 e BRS 226/CP 09